Endothelial venodilator response in carriers of genetic polymorphisms involved in NO synthesis and degradation - Fricker, Ruth; Hesse, Christiane; Weiß, Johanna; Tayrouz Haffar, Yorki Antoine; Hoffmann, Michael Marcus; Unnebrink, Kristina; Mansmann, Ulrich; Haefeli, Walter E. (British journal of clinical pharmacology, 2004)
Aims Polymorphisms of the NOSIII gene and of the CYBA gene have been associated with a number of pathological conditions such as arterial hypertension, coronary artery disease, and myocardial infarction. Because endothelium-dependent vasodilation is impaired in these disorders, we hypothesized that polymorphisms of NOSIII or CYBA might modulate endothelial function of venous capacitance vessels already before cardiovascular disease becomes overt. Methods Endothelium-dependent and -independent venodilation was assessed by measuring local vascular responses to bradykinin and sodium nitroprusside in the dorsal hand vein after preconstriction with phenylephrine in 72 healthy male Caucasians after careful exclusion of cardiovascular risk factors. Genotyping was performed for polymorphisms of the NOSIII gene (T-786C, G894T, (CA)n) and the CYBA gene (C242T). Results Genotype distribution for each polymorphism followed the Hardy-Weinberg equilibrium. In all studied single nucleotide polymorphisms no significant difference between the respective genotypes and the venodilator response to either sodium nitroprusside or bradykinin was observed, and the number of CA repeat copies was not related to the venodilator response to bradykinin. Mean venodilation induced by bradykinin 50 ng min−1 (±SEM) for homozygote carriers of the single nucleotide polymorphisms was 48.9 ± 8.5% venodilation (G894T; wild type: 49.8 ± 6.9), 50.3 ± 11.0% venodilation (T-786C; wild type: 42.6 ± 5.2), and 30.4 ± 9.1% venodilation (C242T; wild type: 49.2 ± 6.0), respectively. Conclusions This study suggests that the studied polymorphisms of NOSIII and CYBA do not significantly modulate endothelium-dependent venodilation in individuals without vascular risk factors.
Gesehen am 19.05.2021